The impact of elevated body core temperature on critical power as determined by a 3-min all-out test - Kaiser, B. W.; Kruse, K. K.; Gibson, B. M.; Santisteban, K. J.; Larson, E. A.; Wilkins, B. W.; Jones, A. M.; Halliwill, J. R.; Minson, C. T. (Journal of Applied Physiology, 2021)
Critical power (CP) delineates the heavy and severe exercise intensity domains, and sustained work rates above CP result in an inexorable progression of oxygen uptake to a maximal value and, subsequently, the limit of exercise tolerance. The finite work capacity above CP, W', is defined by the curvature constant of the power-duration relationship. Heavy or severe exercise in a hot environment generates additional challenges related to the rise in body core temperature (Tc) that may impact CP and W'. The purpose of this study was to determine the effect of elevated Tc on CP and W'. CP and W' were estimated by end-test power (EP; mean of final 30 s) and work above end-test power (WEP), respectively, from 3-min "all-out" tests performed on a cycle ergometer. Volunteers (n = 8, 4 female) performed the 3-min tests during a familiarization visit and two experimental visits (thermoneutral vs. hot, randomized crossover design). Before experimental 3-min tests, the subjects were immersed in water (thermoneutral: 36°C for 30 min; hot: 40.5°C until Tc was =38.5°C). Mean Tc was significantly greater in the hot condition than in the thermoneutral condition (38.5 ± 0.0°C vs. 37.4 ± 0.2°C; means ± SD, P < 0.01). All 3-min tests were performed in an environmental chamber [thermoneutral: 18°C, 45% relative humidity (RH); hot: 38 °C, 40% RH]. EP was similar between thermoneutral (239 ± 57 W) and hot (234 ± 66 W; P = 0.55) conditions. WEP was similar between thermoneutral (10.9 ± 3.0 kJ) and hot conditions (9.3 ± 3.6; P = 0.19). These results suggest that elevated Tc has no significant impact on EP or WEP.